2012
DOI: 10.5923/j.food.20120201.03
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Pasteurization for Food Industry

Abstract: This article reviews the status and scope of ultraviolet (UV) light technology in food processing industry for control of foodborne pathogens and spoilage organisms for food safety and shelf life extension. The literature suggests that there have been extensive studies on application of ultraviolet light for disinfection of apple ciders. FDA acceptable reduction of pathogens and spoilage organisms were reported by UV treatment of for apple cider. Several recent studies on UV treatment of milk suggest that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 26 publications
2
45
0
5
Order By: Relevance
“…Among the three regions, UVA owns the maximum penetration but the lowest energy, while UVC owns the highest energy but the minimum penetration. UVC is often used to control foodborne pathogens and spoilage organisms for food safety and shelf life extension due to its tremendous damage to the DNA of microorganism (Bintsis, LitopoulouTzanetaki, & Robinson, 2000;Choudhary & Bandla, 2012).…”
Section: Factors Influencing the Uv Detoxification Efficiency Of Aflamentioning
confidence: 99%
“…Among the three regions, UVA owns the maximum penetration but the lowest energy, while UVC owns the highest energy but the minimum penetration. UVC is often used to control foodborne pathogens and spoilage organisms for food safety and shelf life extension due to its tremendous damage to the DNA of microorganism (Bintsis, LitopoulouTzanetaki, & Robinson, 2000;Choudhary & Bandla, 2012).…”
Section: Factors Influencing the Uv Detoxification Efficiency Of Aflamentioning
confidence: 99%
“…The efficacy of UV radiation to control pathogens in apple cider has been the focus of different studies (Wright et al 2000;Hanes et al 2002;Basaran et al 2004, Choudhary andBandla 2012). Choi and Nielsen (2005) demonstrated that UV pasteurized apple cider was superior in color and overall sensory scores compared to thermally pasteurized apple cider.…”
Section: Introductionmentioning
confidence: 98%
“…In the study of Jean et al (2011), pulsed UV light at 60 mWs/cm 2 and 91 mWs/cm 2 induced complete reduction (5 log cycle) of MNV-1 and norovirus-1 and HAV, respectively on stainless steel. Pulsed UV light is more effective and rapid infection of inactivating microorganisms than conventional (continuous) UV light (Jean et al, 2011) whereas this radiation technology is expensive (Choudhary and Bandla, 2012). It is well predictable because it depends on the amount of energy delivered and absorbed by the sample.…”
Section: Introductionmentioning
confidence: 99%